Implementasi Rapid Application Development dan Evaluasi User Experience Questionnaire pada Sistem Informasi Pendaftaran PKL Berbasis Website di UMNU Kebumen - Rifki Ardiansah; Ghufron Zaida Muflih (JSAI (Journal Scientific and Applied Informatics), 2026)
Field Work Practice (PKL) as a mandatory curriculum component at Ma'arif Nahdlatul Ulama University (UMNU) Kebumen still faces administrative challenges such as data duplication, non-real-time quota validation, and non-integrated payment verification. Unlike similar systems that focus only on basic registration, this study develops a web-based PKL registration information system by integrating real-time quota validation features and a payment verification mechanism by the treasurer. The system was developed using the Rapid Application Development (RAD) method to accelerate the development process. The system was built with the Laravel framework and MySQL. Functional testing results show that all features run with 100% accuracy. Evaluation using the User Experience Questionnaire (UEQ) on 42 respondents yielded positive scores on six aspects: attractiveness (1.623), clarity (1.524), efficiency (1.655), accuracy (1.589), stimulation (1.601), and novelty (1.244). The system has been proven to optimize the PKL administrative process and can serve as a model for developing integrated systems in higher education institutions.